Query Suggestion based on User Landing Pages - Cucerzan, Silviu; White, Ryen W. (Proceedings of SIGIR 2007, 2007)
This poster investigates a novel query suggestion technique that selects query refinements through a combination of many users’ post-query navigation patterns and the query logs of a large search engine. We compare this technique, which uses the queries that retrieve in the top-ranked search results places where searchers end up after post-query browsing (i.e., the landing pages), with an approach based on query refinements from user search sessions extracted from query logs. Our findings demonstrate the effectiveness of using landing pages for the direct generation of query suggestions, as well as the complementary nature of the suggestions it generates with regard to traditional query log based refinement methodologies.